2014
DOI: 10.4236/aim.2014.48050
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Alkaliphilic Isolate of <i>Bacillus mannanilyticus</i>, Strain IB-OR17, Displaying Chitinolytic and Antifungal Activities

Abstract: How to cite this paper: Melentiev, A.I., et al. (2014) AbstractThe novel alkaliphilic strain, designated as Bacillus sp. IB-OR17 and isolated from soda lake sediments, was identified and characterized. Isolated strain demonstrated slight antifungal activity against some plant pathogen fungi that are capable to grow under alkaline conditions. Based on its morphological, physiological and biochemical characteristics as well as on 16S rRNA gene analysis data, Bacillus sp. IB-OR17 were related to alkaliphilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…CS495 that were active from pH 8.0 to 13.6 with the highest activity at pH 12.5 [48], but the tested enzyme is stable at thermal conditions plus alkaline one. These results are compatible with data revealed that the enzymes worked under alkaline conditions with high potentiality and could be used in many applications [49,50].…”
Section: Resultssupporting
confidence: 91%
“…CS495 that were active from pH 8.0 to 13.6 with the highest activity at pH 12.5 [48], but the tested enzyme is stable at thermal conditions plus alkaline one. These results are compatible with data revealed that the enzymes worked under alkaline conditions with high potentiality and could be used in many applications [49,50].…”
Section: Resultssupporting
confidence: 91%
“…It has advantage instead other enzymes as it is thermoalkaliphile enzymes and resistant to a wide range of environment conditions. Protease, pectinase and cellulases can be applied in agricultural field for plant pathogens controlling as safe antifungal and antinematodal agents [79,80]. Also, these enzymes used for bioenergy production from agricultural wastes by degrading agricultural wastes as ecofriendly agents [81,82].…”
Section: Optimization Of Beneficial Enzymes Productionmentioning
confidence: 99%
“…To date, many microbial strains, such as yeast, bacteria, and filamentous fungi, have been used for the control of mold contamination. The biological control mechanism mainly involves the production of direct antifungal substances, such as non-volatile metabolites [ 8 ], volatile organic compounds (VOCs) [ 9 , 10 ] and extracellular lytic enzymes [ 11 ]. Among the microbial strains associated with the biological control mechanism, the broad-spectrum antagonistic Bacillus has gradually become one of the most valuable, because of its good biological activity, high inhibitory activity to a variety of pathogenic microorganisms, and convenient mass production [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%